Comprehensive Analysis of a Recalled Modular Total Hip System and Recommendations for Management. (6th January 2016) - Nawabi, Danyal H.; Do, Huong T.; Ruel, Allison; Lurie, Brett; Elpers, Marcella E.; Wright, Timothy; Potter, Hollis G.; Westrich, Geoffrey H.
Abstract : Background: Recent total hip arthroplasty designs have introduced modularity at the neck-stem junction. There are reports of failure of this class of designs due to corrosion at the modular junction. The purpose of this study was to evaluate patients implanted with a recently recalled modular total hip arthroplasty system. Methods: This was a prospective study of 216 total hip arthroplasties in 195 patients performed by a single surgeon. All hips had a titanium-alloy stem, but 199 had a modular cobalt-chromium neck and seventeen were monolithic. The mean patient age was 65.4 years (range, twenty to eighty-eight years); seventy-nine were men and 116 were women. Patients were evaluated for infection and with metal ion assays and MRI (magnetic resonance imaging). Intraoperative tissue samples were graded, and retrieved implants were examined. Results: At a mean follow-up of 19.3 months, eighty (37%) of 216 hips had been revised. An adverse local tissue reaction (ALTR) was the cause for revision in seventy-three of these eighty hips; all had the modular neck design. Assay results for the patients requiring revision showed higher levels of cobalt (mean, 8.6 ng/mL) than chromium (mean, 1.8 ng/mL). MRI showed moderate to severe levels of synovial response in sixty-three of 166 hips. The mean ALVAL (aseptic lymphocyte-dominated vasculitis-associated lesion) score for the revised hips was 8.1. Corrosion was visible on all tapers at the neck-stem junction but not the head-neck junction. Conclusions: Early failures of modular total hip arthroplasty occur due to fretting and corrosion at the neck-stem junction, resulting in ALTR. Surveillance utilizing metal ion levels and MRI may be indicated for all patients regardless of symptoms, as the early survivorship is poor and the ultimate failure rate may be catastrophically high. Level of Evidence: TherapeuticLevel II . See Instructions for Authors for a complete description of levels of evidence.